Black migrants in Brazilian and South African tabloids: Representations on the Global South. (1st June 2020) - Araújo, Gilberto Alves
This work investigates how Afro-migrants are represented within a Brazilian and a South African tabloid in terms of race and ethnicity. It also employs scorpus linguistics and critical discourse analysis to analyse verbal language. Results suggest that the two newspapers represent black migrants in the light of criminality, either as victims or perpetrators. They often place migrants as beneficiaries of charity, especially in the Brazilian case, and more as perpetrators in the South African case. Passivization of migrants is noticeable in both tabloids; however, the Brazilian outlet resorts mostly to reported speech and editing of the migrants' voices while the South African offers them either freer speech or silencing. Ultimately, Afro-Latin philosophical principles such as self-determination and empathetic zeal are often times neglected across many depictions.